Certain mean-type fractional integral inequalities via different convexities with applications - Muhammad Samraiz; Fakhra Nawaz; Sajid Iqbal; Thabet Abdeljawad; Gauhar Rahman; Kottakkaran Sooppy Nisar (Journal of Inequalities and Applications, 2020)
Abstract In this paper, we establish certain generalized fractional integral inequalities of mean and trapezoid type for ( s + 1 ) $(s+1)$ -convex functions involving the ( k , s ) $(k,s)$ -Riemann–Liouville integrals. Moreover, we develop such integral inequalities for h-convex functions involving the k-conformable fractional integrals. The legitimacy of the derived results is demonstrated by plotting graphs. As applications of the derived inequalities, we obtain the classical Hermite–Hadamard and trapezoid inequalities.